Rancang Bangun Perpustakaan Digital Berbasis Document Management System pada Fakultas Ilmu Komputer UNSIKA - Yayan Gustiana; Jajam Haerul Jaman; Nono Heryana (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
A book is a reading tool for everyone, it is very important for an institution to keep knowledge going and generate new knowledge. In the library of the Faculty of Computer Science Unsika, one of the obstacles that is the library space where the books are less adequate and difficult to find the title of research for final students because the title should not be the same. Development of a library with Document Management System based is a method in solving the problem, it is expected to provide solutions in achieving a document management. Can accommodate all books uploaded by users, given permissions and speed in the deployment to all users. Development of this modeling tool using the method. Which is in accordance with the wishes of customers. Database storage using MySQL, Object Oriented Programming (OOP) programming language using the Code Igniter (CI) framework. Based on the results of simple random sampling of 35 respondents 86.80% say agree to the digital library. the concept of document management system required large storage media, server and good local connectivity. This function can also be a stepping stone to do research.